دور النشاط البدني الرياضي المكيف في التقليل من السلوك العدواني لدى الأطفال المعاقين ذهنيا القابلين للتعلم من وجهة نظر المربين - دراسة ميدانية بالمركز الطبي التربوي للمتخلفين عقليا بالمسيلة- - صغيري, رابح (Université de M'sila, 2013)
هدفت الدراسة إلى إبراز أهمية ودور النشاط البدني الرياضي المكيف في التقليل من السلوك العدواني للأطفال المعاقين ذهنيا القابلين للتعلم من وجهة نظر المربين"، داخل المركز الطبي التربوي للمتخلفين عقليا بالمسيلة . أجريت الدراسة بالمركز الطبي التربوي للمتخلفين عقليا بالمسيلة على عينة تتكون من 27مربي، من بينهم 17 مربي نظريا و10مربي تطبيقي(ميداني )، وبالاعتماد على المنهج الوصفي الذي يعد من ابرز المناهج استخداما في العلوم الاجتماعية والنفسية، وباستخدام استمارة الاستبيان مصممة من طرف الباحث الموجهة إلى المربين المؤطريين بالمركز من أجل معرفة خصائص و سمات ذوي التخلف الذهني القابلين للتعلم، معرفة العلاقة الارتباطين بين ممارسة النشاط البدني الرياضي المكيف و التقليل من السلوك العدواني لدى هذه الفئة، معرفة الدور الفعال للنشاط البدني الرياضي المكيف في تغيير السلوك العدواني للأطفال المعاقين ذهنيا القابلين للتعلم. وبعد جمع المعلومات والبيانات كانت النتائج المتوصل إليها مشجعة ومفيدة أعطت بعدا أعمق للبحث، وتبين في الأخير أن للنشاط البدني الرياضي المكيف بديل من البدائل التي يمكن من خلالها أن نحافظ على ذوي الاحتياج الخاص ذهنيا، والنشاط البدني المكيف مصدر من مصادر الفرح والبهجة والسرور لذوي التخلف الذهني، ومن خلال الممارسة البدنية الرياضية المكيفة تتكون لذوي التخلف الذهني سلوك مقبول اتجاه نفسه ومجتمعه. ومن ابرز الخطوات التي تم التوصل أليها في نهاية البحث كانت على النحو التالي:  العمل على ضرورة وجود أخصائي رياضي مكيف في المراكز الطبية التربوية لذوي التخلف الذهني. إدماج حصة النشاط البدني المكيف ضمن الأهداف العامة للتربية الخاصة بذوي التخلف الذهني الخوض في دراسات مستقبلية تتناول أهمية النشاط البدني المكيف الموجه لذوي التخلف الذهني. الملخص باللغة الأجنبية: The summary The study aimed to show the importance and the role of the adapted sport physical activity In the reduction of the violent behavior for the mental handicapped children who are accepted for learning according to specialists incident the educational medical centre for in m*sila. The study made in the medical education centre for the mental handicapped in m*sila. On sample group of 27 teachers among them 17 theoretical and 10 practical teachers depending on the descriptive method which is considered as one of the most used methods in the psycho social sciences and by using the survey which is designed by the researcher that is directed to the teachers in side the centre in order to know the characteristics of the mental handicapped who are acceptable for the learning to know the relation ship between the practice of the adapted sport physical activity and the reduction from the violent behavior for this group. Knowing the efficient role of the adapted sport physical activity in changing the violent behavior for the mental handicapped children who are accepted to learn. After gathering the data the results were very encouraging and useful. It gave a deep diminution for the research. It showed that for the adapted sport physical activity a great importance in preserving the mental handicapped children .it is considered as a source of joy and happiness for them . Among the achieved objectives of the research are. _the necessity of finding an adapted sport specialist in the educational medical centers for the mental handicapped person . _entering of the adapted sport physical activity section in the general objectives of teaching this group . _making a future studies which…. talk about the importance of the adapted sport physical activity directed to the mental handicapped persons .
Keywords: النشاط البدني الرياضي المكيف السلوك العدواني الأطفال المعاقين ذهنيا القابلين للتعلم